Local Wisdom as an Effort for Sustainable Fisheries Resource Management: A Case Study in Lake Tempe, Wajo Regency, South Sulawesi - Neneng Rahayu Ningsih; Fitri Hardianti Wijaya; Mirdah Aprilia Amir; Yusran; Riswan Dugo (Jurnal Studi Perikanan Berkelanjutan, 2025)
Local wisdom represents a system of knowledge, norms, and practices derived from the interaction between communities and their environment, including the utilization of fishery resources. This study aims to explore various forms of local wisdom among the fishing communities of Lake Tempe, Wajo Regency, and their role in supporting sustainable fisheries management. The research employed a descriptive qualitative approach, using data collection techniques such as in-depth interviews, participatory observation, and literature review. Thematic analysis was conducted by categorizing findings based on customary rules, fishing practices, sanction mechanisms, and social values that uphold ecosystem sustainability. The results reveal that the Lake Tempe community maintains traditional regulations such as prohibiting fishing during spawning seasons, using environmentally friendly fishing gear, and allocating fishing zones based on customary knowledge. Furthermore, social sanctions serve as a mechanism for ensuring community compliance with collective norms. These findings confirm that local wisdom not only sustains ecosystem balance and fish stocks but also strengthens social cohesion among fishers. The discussion emphasizes the need to integrate local wisdom into formal policy through a co-management model involving local governments, fishing communities, and other stakeholders. In conclusion, local wisdom holds significant potential as a key pillar for sustainable fisheries resource management in Lake Tempe.